Adsorption–desorption behavior of halloysite clay for Cu2+ ions and recovery of copper by electrodeposition method - Le Thi Duyen; Bui Hoang Bac (Desalination and Water Treatment)
Halloysite sample, obtained from Phu Tho province, Vietnam, was utilized to investigate the adsorption behavior of Cu2+ ions. Several factors influencing Cu2+ adsorption efficiency and capacity were explored, including pH value, contact time, adsorbent dose, and initial Cu2+ concentration. Under optimal conditions (0.8 g of halloysite per 50 mL of solution, an initial Cu2+ concentration of 40 mg/L, pH 6.2, a contact time of 80 min, and a temperature of 25 °C), the study yielded an adsorption efficiency of 85.19% and a capacity of 2.14 mg/g for Cu2+ ions. Adsorption isotherm analysis was conducted using the Langmuir and Freundlich models, while the kinetics of the adsorption process were investigated through the first-order pseudo and second-order pseudo models. Furthermore, the desorption of Cu2+ ions and the recovery of Cu metal were explored, with a recovery efficiency of Cu reaching 94.65% under suitable conditions (0.3 g mass of halloysite, a current of 7.5 mA, and an electrolytic time of 5 h at 60 °C). These findings suggest the potential application of halloysite clay for removing Cu2+ ions from polluted water, recovering Cu metal, and reusing the adsorbent.